Taxonomic review of Drilus Olivier, 1790 (Elateridae: Agrypninae: Drilini) from Asia Minor, with descriptions of seven new species and comments on the female antennal morphology in Drilini - Kobieluszova, Lucie; Kundrata, Robin (Zootaxa, 2015)
The neotenic elaterid genus Drilus Olivier, 1790 in Asia Minor is reviewed. Twelve species are recognized, of which seven are described as new: Drilus badius sp. nov., D. huijbregtsi sp. nov., D. mertliki sp. nov., D. robustus sp. nov., D. sanliurfensis sp. nov., D. teunisseni sp. nov., and D. turcicus sp. nov. All known species are listed with diagnoses, data on variability and distribution. A key to the males of Drilus species in Asia Minor is provided and information on prey of known larvae is summarized. Antennal morphology of Drilini females is briefly discussed.